MPs on the Subject of STEMM: What Can Oral History Tell Us?. - Ledgerwood, Emmeline (Parliamentary History, 2020)
A growing collection of archived oral history interviews with former MPs offers historians new opportunities to study the influences that have directed MPs' routes into elected office and their behaviour in the house of commons. This article draws on evidence in the interviews to consider the extent to which an MP's background in science, technology, engineering, maths, and medicine (so‐called STEMM subjects) has contributed to his or her activity as a parliamentarian. When concerns are raised about the House's capacity to effectively debate and scrutinise legislation concerning STEMM matters, those concerns are often accompanied by calls for more MPs with a STEMM background. Listening to these oral history interviews to hear what individual MPs say about their connections with STEMM – whether before, during, or after their time in the Commons – provides an insight into the relevance of having a STEMM background as an MP and offers explanations as to why MPs with a STEMM background are in a minority in the House. As such, this examination of historical material contributes to the ongoing debate about the role of STEMM experts in parliament while demonstrating the value of consulting archived oral history interviews when researching 20th‐century parliamentary history.